Nanoparticle Emission and Characterization from Pre-Dried Lignite and Bituminous Coal Co-Combustion - Ioannis Avagianos; Panagiotis Vounatsos; Ioannis Papandreou; Joerg Maier; Panagiotis Grammelis; Emmanuel Kakaras (Energies, 2020)
Nowadays, the high share of electricity production from renewables drives coal-fired power plants to adopt a more flexible operation scheme and, at the same time, maintain flue gas emissions within respective standards. A 500 kWth pulverized coal furnace was used to study pre-dried lignite combustion or co-combustion as an available option for these plants. Bituminous coal from Czech Republic and pre-dried lignite from Greece were blended for the experiments. Particle emissions measurements with a heated Electrical Low Pressure Impactor (ELPI+) and Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM/EDS) analyses were performed. The effect of the pre-dried lignite proportions in the fuel feed and the combustion conditions regarding the combustion air staging were the two parameters selected for this study. Skeletal density values were measured from the cyclone prior to the impactor. Results are depicted with respect to the aerodynamic and Stokes diameter for impactor stages. The presence of pre-dried lignite in the fuel blend lowers the particle matter (PM) PM2.5, PM1 and PM0.1 emissions, thus having a positive impact on ESP’s fractional and overall efficiency. The staged combustion air feed reduces the particle emissions in all cases. Sulfur content follows a pattern of higher concentration values for finer particles.